2022
DOI: 10.1177/01945998221119730
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Intensive Care Unit Admission Following Cleft Palate Repair by Head and Neck Surgeons

Abstract: Objective To examine the incidence of pediatric intensive care unit (PICU) admission following primary repair of cleft palate by otolaryngologist–head and neck surgeons at 2 tertiary centers. To identify potential diagnoses associated with admission or unanticipated PICU transfer. Study Design Multi-institutional case series with chart review. Setting Two tertiary pediatric medical centers. Methods Children who underwent primary repair of cleft palate at 2 cleft centers over a 10-year period were identified. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(85 reference statements)
2
0
0
Order By: Relevance
“…Additionally, a recent study of a cohort of 433 patients with significant syndromic and non-syndromic comorbidities treated by otolaryngology have shown that planning and unplanned Pediatric Intensive Care Unit admissions were low (approximately 7.0%). 21 Notably, PICU admission rates within this study were similar to previously described studies that had a smaller comorbidity burden. The most benign possibility is some form of reporting bias, as the NSQIP-P does not represent all institutions in the United States and therefore could represent facilities with higher complication rates compared with those that are unrepresented.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, a recent study of a cohort of 433 patients with significant syndromic and non-syndromic comorbidities treated by otolaryngology have shown that planning and unplanned Pediatric Intensive Care Unit admissions were low (approximately 7.0%). 21 Notably, PICU admission rates within this study were similar to previously described studies that had a smaller comorbidity burden. The most benign possibility is some form of reporting bias, as the NSQIP-P does not represent all institutions in the United States and therefore could represent facilities with higher complication rates compared with those that are unrepresented.…”
Section: Discussionsupporting
confidence: 86%
“…Another possibility includes treating more complex children with higher rates of comorbidities that make them prone to poor wound healing and subsequently more complications; this seems unlikely though, as our study demonstrated that otolaryngology performs more cleft repairs on these high‐risk patients, but do not have a higher rate of complication. Additionally, a recent study of a cohort of 433 patients with significant syndromic and non‐syndromic comorbidities treated by otolaryngology have shown that planning and unplanned Pediatric Intensive Care Unit admissions were low (approximately 7.0%) 21 . Notably, PICU admission rates within this study were similar to previously described studies that had a smaller comorbidity burden.…”
Section: Discussionsupporting
confidence: 83%